CONVERSION OF SUGARS INTO 5-HMF - Amutha Chinnappan; Shikha Baskar; Chinnappan Baskar (Pattimura University, 2017)
At present, fossil fuels are playing the major role to meet the energy requirements of the world. The large consumption of fossil fuels creates so many environmental problems, such as green-house gases have motivated the search for alternative, renewable fuel options. Biomass is one of the few resources that have the potential to meet the challenges of sustainable and green energy systems. Current biomass resources comprise primarily industrial waste materials such as sawdust or pulp process wastes, hog fuel, forest residues, clean wood waste from landfills, and agricultural prunings and residues from plants such as lignocellulosic materials. There are already a considerable range of chemical building blocks derived from renewable resources. Among them, 5-hydroxymethylfurfural (HMF) is a versatile platform chemical for the synthesis of a wide range of industrially important materials, including biofuels.